Geometry Learning Design Through Ethnomathematics of Gandrung Fashion and Accessories - Ainia, Vera Masrurotul; Mariana, Neni; Indrawati, Delia (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to describe students' exploration activities regarding Ethnomathematics using student worksheets with the RME approach. This study is a design study designed through the inherent assumptions of the learning trajectory hypothesis analysis framework (HLT), which is then tested in realistic mathematics education (RME). Gandrung is a traditional dance from Banyuwangi. Through Gandrung clothing and accessories, students can learn basic geometry. The design of this study was carried out in three stages, namely, initial design, experimental learning consisting of 2 cycles, and the third stage of analysis, namely retrospective. This study used a sample of 28 second-grade students in the Surabaya area, comprising six students in Cycle I and 22Â in Cycle II. Students conducted the study's results to understand the concept of geometry and show that measurements can trigger the occurrence of a learning trajectory. The impact on students can be seen at the learning stage: observing certain parts of the picture, paying attention to exciting patterns/decorations, and aligning parts of the image. Students can simply conclude the results of the formation of basic concepts of flat plane geometry and its transformations.